Demographic and clinical profile of cardioembolic stroke patients in Western Sydney. Issue 6 (14th June 2020) - Ferkh, Aaisha; O'Keefe, Emily; Zada, Matthew; Brown, Paula; Duggins, Andrew; Thiagalingam, Aravinda; Altman, Mikhail; Byth, Karen; Kizana, Eddy; Denniss, Alan R.; Thomas, Liza
Abstract: Background: Cardioembolism (CE) contributes to a large proportion of ischaemic stroke. Aims: To evaluate the demographic and clinical profile of CE stroke in Western Sydney. Methods: A retrospective analysis of ischaemic stroke patients presenting to Westmead Hospital (January–October 2016) was performed. Strokes were classified by TOAST (Trial of Org 10172 in Acute Stroke Treatment) criteria into different categories. Clinical and demographic data were collected on all stroke patients, and differences between CE and other stroke causes were identified. Results: Two hundred and twenty‐eight consecutive patients (70.9 years; 53% male) were identified. By TOAST criteria, 21 (9%) had large‐artery atherosclerosis, 94 (41%) CE, 10 (5%) small‐vessel disease, 2 (1%) other aetiology and 101 (44%) undetermined aetiology. A significant proportion of CE stroke patients had cardiovascular risk factors including hypertension (66%), hypercholesterolaemia (50%), diabetes (26%) and ischaemic heart disease (28%). The majority (81%) of patients with CE had atrial flutter/flutter. CE stroke, compared with other types of stroke, was more common in females (56 vs 41%, P = 0.022) and patients with CE stroke were more likely to have previous cerebral ischaemia (34 vs 21%, P = 0.026), suggesting increased recurrence in this group. Of the patients with atrial flutter/flutter ( n = 56), the majority (87%) had a high CHA2 DS2 ‐VASC score (≥2); however, a significant proportion (55.4%) were not on anticoagulation. Conclusions: Cardioembolic stroke remains a significant burden in Western Sydney, and it is likely that a significant proportion may be preventable, as evidenced by the substantial presence of modifiable cardiovascular risk factors, and inadequate anticoagulation of patients with atrial arrhythmias.